Analysis of the Influence of Country of Origin, Brand Awareness, and Perceived Price on The Purchase Decision of MCB Client Products with Perceived Quality as A Mediating Variable - Biko Yoshia Sirus (Journal Of Social Science (JoSS), 2023)
The purpose of this study is to test and analyze the influence of country of origin, brand awareness, and perceived price on the purchase decision of MCB CHINT products with perceived quality as a mediation variable. The data used in this study are the results of questionnaires distributed directly in March - April 2023. Sampling is done through the purposive sampling method, where researchers have set several criteria. There were 149 respondents in this study. This research analysis method uses PLS-SEM with the help of SMART PLS. Perceived Quality mediates the influence of Country of Origin on Purchase Decisions partially (Partial Mediation). Perceived Quality does not mediate the influence of Brand Awareness on Purchase Decision (No Mediation) Perceived Quality fully mediates the influence of Perceived Price on Purchase Decision (Full Mediation).